Investigating the Mechanical and Durability Properties of Carbonated Recycled Aggregate Concrete and Its Performance with SCMs - Shimza Jamil; Maria Idrees; Arslan Akbar; Wisal Ahmed (Buildings)
Utilizing recycled aggregates (RAs) in concrete production represents a promising path toward sustainability; however, it often results in reduced physical and durability properties. The weak interfacial transition zone (ITZ) and the adhered mortar in recycled aggregate concrete (RAC) contribute to lower mechanical strength and limit its application in demanding environments. This study investigates an accelerated carbonation technique to enhance the mechanical and durability properties of RA and RAC. Recycled aggregates, with a particle size of 10–20 mm, were subjected to carbonation at 1 bar for 2 h in a controlled carbonation chamber. Results demonstrate substantial improvements in the compressive and split tensile strengths of the carbonated recycled aggregate concrete (CRAC), with increases of 30% and 42% compared to conventional RAC, respectively. The CRAC mix also exhibited a 1.5% increase in dry density and reduced water absorption (6%) compared to RAC (7.58%). After 90 days of acid exposure, compressive strength reductions of 48.85% and 37.9% were observed for RAC and CRAC mixes, respectively, from their 28-day strength, while weight loss in CRAC was limited to 5.4%, compared to 10.92% in RAC. In sulfate exposure tests over 150 days, RAC and CRAC showed compressive strength reductions of 31.4% and 19.7% and weight losses of 3.6% and 2.2%, respectively, indicating enhanced resistance of CRAC to harsh environments. However, CRAC blended with supplementary cementitious materials (SCMs) showed diminished mechanical properties, likely due to a reduced alkaline environment caused by rapid calcium hydroxide absorption in RA pores during carbonation. Overall, the findings highlight the practical potential of accelerated carbonation to improve the performance of RAC, offering a viable pathway for sustainable construction applications.